.5(9x+18)=-1.5(5x)-2(3x+3.5)

Simple and best practice solution for .5(9x+18)=-1.5(5x)-2(3x+3.5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5(9x+18)=-1.5(5x)-2(3x+3.5) equation:


Simplifying
0.5(9x + 18) = -1.5(5x) + -2(3x + 3.5)

Reorder the terms:
0.5(18 + 9x) = -1.5(5x) + -2(3x + 3.5)
(18 * 0.5 + 9x * 0.5) = -1.5(5x) + -2(3x + 3.5)
(9 + 4.5x) = -1.5(5x) + -2(3x + 3.5)

Remove parenthesis around (5x)
9 + 4.5x = -1.5 * 5x + -2(3x + 3.5)

Multiply -1.5 * 5
9 + 4.5x = -7.5x + -2(3x + 3.5)

Reorder the terms:
9 + 4.5x = -7.5x + -2(3.5 + 3x)
9 + 4.5x = -7.5x + (3.5 * -2 + 3x * -2)
9 + 4.5x = -7.5x + (-7 + -6x)

Reorder the terms:
9 + 4.5x = -7 + -7.5x + -6x

Combine like terms: -7.5x + -6x = -13.5x
9 + 4.5x = -7 + -13.5x

Solving
9 + 4.5x = -7 + -13.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13.5x' to each side of the equation.
9 + 4.5x + 13.5x = -7 + -13.5x + 13.5x

Combine like terms: 4.5x + 13.5x = 18x
9 + 18x = -7 + -13.5x + 13.5x

Combine like terms: -13.5x + 13.5x = 0.0
9 + 18x = -7 + 0.0
9 + 18x = -7

Add '-9' to each side of the equation.
9 + -9 + 18x = -7 + -9

Combine like terms: 9 + -9 = 0
0 + 18x = -7 + -9
18x = -7 + -9

Combine like terms: -7 + -9 = -16
18x = -16

Divide each side by '18'.
x = -0.8888888889

Simplifying
x = -0.8888888889

See similar equations:

| x+(3+x)+2x= | | x+0.075x=2150 | | 5x(v+3)= | | 20c^4-41c^2+20= | | Yz=2x+7 | | 99c+44c= | | 10x-2(x-4)=60-3(x+4) | | x+0.075x=1935 | | 5+8(8+5n)= | | P+-26=16 | | 4p+10= | | -37+3v=-4(2-8v) | | 76=11x | | 64r^2-144rf+81f^2= | | 16+(x*x)=41 | | 2x+3y-5x+2y=0 | | x+0.075=1935 | | 2x+2=6(4x+4) | | 2(x+1)=8(x-2)-12 | | 3(x+4)=4x+2 | | c=39.55+0.25x | | 16-6x+4=6 | | (4-3x)-2(5x+7)= | | 10x-2+12=10 | | 8y/2y^3 | | 9y-7y-4=24.50 | | 5/x=15/27 | | 8y-(8-y)=28 | | -1.1-4x-3.1-2x=-5x-3.3 | | 3p(p-2)-2p(3p-2)= | | 9(x*x)=49 | | x+0.075=2150 |

Equations solver categories